FAKTOR-FAKTOR YANG DAPAT MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN PERTAMBANGAN BATU BARA - Hendra; Janny Rowena (JURNAL CAFETARIA, 2021)
The purpose of this study is to knowing how influence of factors that can affect the capital structure such as profitability, liquidity, business risk, firm size and sales growth on the coal mining companies. The population object in this study are all of the coal mining companies on the Indonesia Stock Exchange listed from 2012 to 2019, and use purposive sampling technique to sampling method, then resulting 64 data and used as samples. The multiple linear regression is used method of analysis in this study. Data analysis in this study is used EViews 10. The results shows that profitability, liquidity, business risk and sales growth hasn’t influence on capital structure, but firm size has a significant and positive influence on capital structure. The firm size has a significant and positive effect on capital structure indicating that companies with larger assets are easier to obtain the loans and the confidence from investors.